Erbium-doped silicon nanocrystals grown by r.f. sputtering method: Competition between oxygen and silicon to get erbium - Cerqueira, M.F.
Erbium doped micro- and nanocrystalline silicon thin films have been deposited by co-sputtering of Er and Si. Films with different crystallinity, crystallite size, hydrogen and oxygen content have been obtained in order to investigate the effect of the microstructure and composition of matrix on the near IR range at 1.54 μm Er-related photoluminescence (PL) properties. The correlation between the optical properties and microstructural parameters of the films is investigated using spectroscopic ellipsometry. It is found that the luminescent properties of these composite films can be understood on the basis of the ellipsometric analysis that reveals the films heterogeneous structure, and that Er-related PL dominates in films with 1-3 nm sized Si nanocrystals embedded in a-Si:H.